2017
DOI: 10.1080/00016357.2017.1412498
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography imaging of superior semicircular canal morphology: a retrospective comparison of cleft lip/palate patients and normal controls

Abstract: SSCD should be considered if a CL/P patient exhibits a vestibular system deficiency. Oral and maxillofacial radiologists should pay attention to SSCD when interpreting CBCT images. Future studies should use high-level spatial resolution CBCT to focus on cleft site and SSCC morphology in larger patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Previous studies showed different rates of SSCD ranging from 3.3% to 16.5% 9,33,34,40,41,42,43,44 The differences in the incidence of SSCD might be related to the differences in slice thickness and imaging modality. Many studies used CT imaging to analyze SSC characteristics.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies showed different rates of SSCD ranging from 3.3% to 16.5% 9,33,34,40,41,42,43,44 The differences in the incidence of SSCD might be related to the differences in slice thickness and imaging modality. Many studies used CT imaging to analyze SSC characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, some previous studies revealed no significant differences in the SSCD thickness based on gender. 34,35,36,37 For instance, Evlice et al 34 and Altun et al 33 reported no significant differences between males and females regarding the SSCD patterns. However, Crovetto et al 38 and Karimnejad et al 39 referred to a significant female predominance for semicircular canal dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Low-dose cone-beam computed tomography (CBCT) is commonly used to visualize the craniofacial area. 13,14 In patients with CLP, CBCT offers precise information about the morphology of the alveolar bone before alveolar bone grafting. 15 However, CBCT can be used to identify suspected hearing problems and improve the education of family members and medical staff working with patients, as well as for more appropriate therapy.…”
Section: Introductionmentioning
confidence: 99%